Biochemical characteristics support the recently described species Karlodinium zhouanum (Gymnodiniales, Dinophyceae). Issue 1 (30th July 2019) - Zhu, Xiaojuan; Zhou, Chengxu; Meng, Ran; Li, Shuang; Fang, Keyi; Luo, Zhaohe; Xu, Jilin; He, Shan; Luo, Qijun; Yan, Xiaojun
SUMMARY: The small athecate dinoflagellate Karlodinium zhouanum is a species recently described in the coastal waters of China. K. zhouanum is morphologically similar to Karlodinium veneficum, a typical ichthyotoxic blooming karlotoxin‐producing species, and it is impossible to distinguish between these two species based on light microscopy. In this study, strains of K. zhouanum isolated from the East China Sea were studied. By analyzing toxins, toxicity, lipid characteristics and typical molecular and physiological traits of this species, K. zhouanum was shown to be nontoxic to brine shrimp and widely spread over the coastal waters of China. No karlotoxin‐like toxin was detected by liquid chromatography‐mass spectrometry (LC–MS). Instead of gymnodinosterol, the critical sterol in toxic K. veneficum, 27(nor)‐24S‐4α‐Methyl‐5α‐ergosta‐8(14)‐en‐3β‐ol (NEE ) was dominant in K. zhouanum, while gymnodinosterol was absent. These sterol characteristics may provide not only support for the species separation between toxic and nontoxic species of Karlodinium but also environmental survey tools to differentiate the contribution of nontoxic Karlodinium strains, which has been unclear until now.